Tropes and figures as arguments in textual criticism? - D. Tóth, Judit (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In the first part of my paper, I present the so-called first homilies of St Gregory of Nyssa delivered in praise of the forty martyrs of Sebaste (Mart Ia and Ib) from two separate angles: on the one hand, focusing on how they can be related to stays of the Cappadocian Father in Sebaste and, on the other hand, identifying what sorts of internal arguments of textual criticism are cited when an effort is made to identify when they were delivered. By giving an overview of the most important research findings, I provide a basis for my query concerning whether certain tropes and rhetorical figures as well as rhetorical-stylistical-poetical solutions could be typical of specific time periods and genres in the oeuvre of the church father and, thereby, serve as arguments of textual criticism for identifying the dates for composition of his works. Using the opening lines of Mart Ib, I focus my investigation on the banquet-simile connected to the figure of yesterday/then and today/now, primarily in the epideictic speeches of the bishop of Nyssa. My conclusion is that this is a valid question, while the text analyses confirm the conventional date (383) identified for the production of Mart Ia and Ib.